Leukemia Inhibitory Factor and Fibroblast Growth Factor 2 Critically and Mutually Sustain Pluripotency of Rabbit Embryonic Stem Cells - Lo, Neng-Wen; Intawicha, Payungsuk; Chiu, Yung-Tsung; Lee, Kun-Hsiung; Lu, Hsi-Chi; Chen, Chien-Hong; Chang, Yong-Hsuan; Chen, Chun-Da; Ju, Jyh-Cherng (Cell transplantation, 2015)
Effects of leukemia inhibitory factor (LIF) and fibroblast growth factor 2 (FGF2) on establishment and maintenance of rabbit embryonic stem cell (rESC) lines were assessed. When grown on MEF feeders, rESC lines derived from fertilized embryos were established and maintained in medium containing paracrine factors LIF (via STAT3) and/or FGF2 (via MEK-ERK1/2 and PI3K-AKT). However, high levels of ERK1/2 and AKT activities in rESCs were crucial for maintaining their undifferentiated proliferation. Although rESCs under the influence of either LIF (500, 1,000, and 2,000 U/ml) or FGF2 (5, 10, and 20 ng/ml) alone had enhanced expression of pluripotency markers, peak expression occurred when both LIF (1,000 U/ml) and FGF2 (10 ng/ml) were applied. Induced dephosphorylation of STAT3, ERK1/2, and AKT by specific inhibitors limited growth of rESCs and caused remarkable losses of self-renewal capacity; therefore, we inferred that STAT3, ERK, and AKT had essential roles in maintaining rESC proliferation and self-renewal. We concluded that LIF and FGF2 jointly maintained the undifferentiated state and self-renewal of rESCs through an integrative signaling module.